Reducing Uncertainty Prior to Job Interviews based on the Linkedin Profile of Achmad Zaky as a Potential Office Supervisor - Angga Guslim (Riviera Publishing, 2023)
The development of social media in everyday life is very rapid, both in personal and professional contexts. LinkedIn, as a social media with a professional concept, has been able to become an intermediary in interpersonal communication. The professional job interview process makes many candidates feel anxious before the selection process. Uncertainty Reduction theory becomes the author's reference in revealing the predictability of the job interview process by the number one leader in the company. This research aims to find out and analyze whether Achmad Zaky's LinkedIn profile account can reduce uncertainty during a job interview with him and to find out and analyze whether Achmad Zaky's LinkedIn profile account can predict the questions he will ask during the interview later. This research uses a qualitative method, which is a comprehensive analysis of all activities to all text and image data listed on his LinkedIn profile account through 3 former candidates who have been interviewed by Achmad Zaky. The results show the predictability of questions from Achmad Zaky in the job interview process, this includes his entire LinkedIn profile account in the form of a brief bio, work experience and community, education history, honorary awards and activities consisting of 7 articles and 180 posts during his tenure at the company.